2020
DOI: 10.1002/ente.202000148
|View full text |Cite
|
Sign up to set email alerts
|

From 1D to 3D: Fabrication of CH3NH3PbI3 Perovskite Solar Cell Thin Films from (Pyrrolidinium)PbI3 via Organic Cation Exchange Approach

Abstract: A new crystal form of 1D perovskite (pyrrolidinium)PbI3 (orthorhombic phase) is synthesized and characterized. The 1D perovskite has a good film formability by solution spin coating and is in situ transformed to 3D CH3NH3PbI3 via the organic cation exchange approach in CH3NH2 atmosphere, which is dense and uniform. The converted 3D perovskite film is used as a light absorber, and the corresponding perovskite solar cell shows a power conversion efficiency of up to 19.2% under simulated 1 sun AM1.5G illumination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…The estimated value of the Δ S (∼8 J mol −1 K −1 ) is associated with the structural transformation from the high-temperature (HT) hexagonal P 6 3 / mmc to the low-temperature orthorhombic Pnma phase. 38,39…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated value of the Δ S (∼8 J mol −1 K −1 ) is associated with the structural transformation from the high-temperature (HT) hexagonal P 6 3 / mmc to the low-temperature orthorhombic Pnma phase. 38,39…”
Section: Resultsmentioning
confidence: 99%
“…35–38 Xu et al showed that the compound has a bandgap allowing broad visible light absorption and crystallizes in the hexagonal P 6 3 / mmc space group (273 K), 38 while the Pnma orthorhombic phase is observed at lower temperatures (173 K). 39 So far, none of the previous studies addressed the topic of phase transition (PT) and its influence on material properties. In order to fill that knowledge gap, we determined the PT temperature of PyrPbI 3 , described its switchable dielectric attributes as well as vibrational features of phases at either side of the PT.…”
Section: Introductionmentioning
confidence: 99%
“…Miao et al synthesized a 1D perovskite, (pyrrolidinium)PbI 3 , with orthorhombic phase. 111 Then, the 1D perovskite was put in CH 3 NH 2 (MA) atmosphere to transform to the 3D MAPbI 3 perovskite. The cation exchange reaction is as follows.C 4 NH 10 PbI 3 (s) + CH 3 NH 2 (g) → CH 3 NH 2 PbI 3 (s) + C 4 NH 9 (g)…”
Section: Mass Transfer-controlled Growthmentioning
confidence: 99%